TALEN-mediated homologous-recombination-based fibroin light chain in-fusion expression system in Bombyx mori - Yu, Shihua; Zheng, Huoqing; Ye, Xiaogang; Dai, Xiangping; Wang, Xinqiu; Zhao, Shuo; Dai, Xiaoyan; Zhong, Boxiong (Frontiers in Bioengineering and Biotechnology, 2024)
Silkworm was the first domesticated insect and has important economic value. It has also become an ideal model organism with applications in genetic and expression studies. In recent years, the use of transgenic strategies has made the silkworm silk gland an attractive bioreactor for the production of recombinant proteins, in particular, piggyBac-mediated transgenes. However, owing to differences in regulatory elements such as promoters, the expression levels of exogenous proteins have not reached expectations. Here, we used targeted gene editing to achieve site-specific integration of exogenous genes on genomic DNA and established the fibroin light chain (FibL) in-fusion expression system by TALEN-mediated homology-directed recombination. First, the histidine-rich cuticular protein (CP) was successfully site-directed inserted into the native FibL, and the FibL–CP fusion gene was correctly transcribed and expressed in the posterior silk gland under the control of the endogenous FibL promoter, with a protein expression level comparable with that of the native FibL protein. Moreover, we showed based on molecular docking that the fusion of FibL with CP may have a negative effect on disulfide bond formation between the C-terminal domain of fibroin heavy chain (FibH) and FibL–CP, resulting in abnormal spinning and cocoon in homozygotes, indicating a significant role of FibL in silk protein formation and secretion. Our results demonstrate the feasibility of using the FibL fusion system to express exogenous proteins in silkworm. We expect that this bioreactor system will be used to produce more proteins of interest, expanding the application value of the silk gland bioreactor.